Neladenoson Bialanate Hydrochloride: A Prodrug of a Partial Adenosine A1 Receptor Agonist for the Chronic Treatment of Heart Diseases. (10th May 2017) - Meibom, Daniel; Albrecht‐Küpper, Barbara; Diedrichs, Nicole; Hübsch, Walter; Kast, Raimund; Krämer, Thomas; Krenz, Ursula; Lerchen, Hans‐Georg; Mittendorf, Joachim; Nell, Peter G.; Süssmeier, Frank; Vakalopoulos, Alexandros; et al.
Abstract: Adenosine is known to be released under a variety of physiological and pathophysiological conditions to facilitate the protection and regeneration of injured ischemic tissues. The activation of myocardial adenosine A1 receptors (A1 Rs) has been shown to inhibit myocardial pathologies associated with ischemia and reperfusion injury, suggesting several options for new cardiovascular therapies. When full A1 R agonists are used, the desired protective and regenerative cardiovascular effects are usually overshadowed by unintended pharmacological effects such as induction of bradycardia, atrioventricular (AV) blocks, and sedation. These unwanted effects can be overcome by using partial A1 R agonists. Starting from previously reported capadenoson we evaluated options to tailor A1 R agonists to a specific partiality range, thereby optimizing the therapeutic window. This led to the identification of the potent and selective agonist neladenoson, which shows the desired partial response on the A1 R, resulting in cardioprotection without sedative effects or cardiac AV blocks. To circumvent solubility and formulation issues for neladenoson, a prodrug approach was pursued. The dipeptide ester neladenoson bialanate hydrochloride showed significantly improved solubility and exposure after oral administration. Neladenoson bialanate hydrochloride is currently being evaluated in clinical trials for the treatment of heart failure. Abstract : Good gets even better : Partial adenosine A1 receptor (A1 R) activation is associated with a positive impact on heart failure without the detriments of full A1 R agonism. Starting from capadenoson, we describe the identification of neladenoson bialanate hydrochloride, which has a good pharmacokinetic and safety profile. Neladenoson bialanate hydrochloride is currently being assessed in clinical studies for the treatment of heart failure.